2013
DOI: 10.2478/10004-1254-64-2013-2248
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Improves Liver Function in Benzene-Treated Rats

Abstract: In this study, we investigated the benefi cial effects of melatonin against benzene-induced liver function impairments in Wistar rats. After 30 days of treatment, it signifi cantly lowered hepatosomatic indices, bilirubin, and hydroxyproline in male and female benzene-treated rats. Even though it did not infl uence aspartate aminotransferase, melatonin had benefi cial effects on alanine aminotransferase and alkaline phosphatase. Our results suggest that melatonin is an effective modulator of liver function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Melatonin has been shown to possess marked antioxidative capacities ( 44 , 45 ) . Indeed, results of animal studies suggest that beneficial effects of melatonin in various settings of liver damage were associated with an attenuation of oxidative and inflammatory damage associated with these diseases ( 46 , 47 ) . It has been shown that treatment with melatonin but also its precursor tryptophan reduced levels of pro-inflammatory cytokines and improved parameters of fat metabolism in patients with NAFLD ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been shown to possess marked antioxidative capacities ( 44 , 45 ) . Indeed, results of animal studies suggest that beneficial effects of melatonin in various settings of liver damage were associated with an attenuation of oxidative and inflammatory damage associated with these diseases ( 46 , 47 ) . It has been shown that treatment with melatonin but also its precursor tryptophan reduced levels of pro-inflammatory cytokines and improved parameters of fat metabolism in patients with NAFLD ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Both have detrimental effects on humans and animals. Benzene could cause liver function impairments and the lipid peroxidation of mitochondria and microsome [22,23]. The protective effects of melatonin on liver injury induced by benzene were identified.…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…The protective effects of melatonin on liver injury induced by benzene were identified. Hepatosomatic indices, bilirubin as well as hydroxyproline in male and female rats treated with benzene were significantly lowered after 30 days’ melatonin treatment (0.25 mL of 2% melatonin) [22]. Mitochondrial and microsomal lipid peroxidation was inhibited by melatonin at the concentration of 10 mg/kg BW.…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…Melatonin may also prevent and treat liver injuries and diseases. Several studies have shown that melatonin has a hepatoprotective effect [35][36][37][38][39].…”
Section: Effect Of the Melatonin On Hepatic Enzymesmentioning
confidence: 99%